Peppa Pig : class trip. - Astley, Neville; Baker, Mark, 1959- (New York, NY : Scholastic Inc., 2013)
Peppa Pig and her classmates take a class trip to a mountain.
"This book is based on the TV series Peppa Pig. Peppa Pig is created by Neville Astley and Mark Baker"--T.p.
2.2
Preschool.
Preschool
Keywords: Mountains -- Juvenile fiction; Peppa Pig (Fictitious character) -- Juvenile fiction; Swine -- Juvenile fiction; Mountains -- Fiction; Peppa Pig (Fictitious character) -- Fiction; Pigs -- Fiction; Mountains -- Fiction; Peppa Pig (Fictional character) -- Fiction; Pigs -- Fiction; Radio and television novels; Picture books for children; Radio and television novels